2023
DOI: 10.3847/1538-4357/acd769
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Energy Budget in the Solar Wind from 13.3 to 100 Solar Radii

Abstract: A variety of energy sources, ranging from dynamic processes, such as magnetic reconnection and waves, to quasi-steady terms, such as plasma pressure, may contribute to the acceleration of the solar wind. We utilize a combination of charged particle and magnetic field observations from the Parker Solar Probe (PSP) to attempt to quantify the steady-state contribution of the proton pressure, the electric potential, and the wave energy to the solar wind proton acceleration observed by PSP between 13.3 and ∼100 sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 103 publications
(145 reference statements)
3
8
0
Order By: Relevance
“…Some contribution to wind driving may also come from the electric potential energy (the third largest energy flux), which furthermore exceeds the kinetic energy term at altitudes slightly less than 6 R e (blue curve). This is in agreement with the results found by Halekas et al (2023), which show that this form of energy can account for proton acceleration of the lower-speed streams. Enthalpy and heat fluxes (green and gray curves, respectively), on the other hand, are expected to become important only much lower, around 2-4 R e , at the temperature maximum (e.g., Antonucci et al 2005).…”
Section: Estimate Of Energy Flux Terms In the Coronasupporting
confidence: 93%
See 2 more Smart Citations
“…Some contribution to wind driving may also come from the electric potential energy (the third largest energy flux), which furthermore exceeds the kinetic energy term at altitudes slightly less than 6 R e (blue curve). This is in agreement with the results found by Halekas et al (2023), which show that this form of energy can account for proton acceleration of the lower-speed streams. Enthalpy and heat fluxes (green and gray curves, respectively), on the other hand, are expected to become important only much lower, around 2-4 R e , at the temperature maximum (e.g., Antonucci et al 2005).…”
Section: Estimate Of Energy Flux Terms In the Coronasupporting
confidence: 93%
“…One viable approach is to consider that their dependence, as derived from PSP observations in the very inner heliosphere at the lowest limit of 13.3 R e also holds slightly below, down to 6.3 R e . Halekas et al (2023) showed that in the slow solar wind the perpendicular component of the proton temperature scales approximately as r −0.25 (in agreement with the results provided by Wu et al 2020), while the parallel component does not exhibit appreciable variation with heliocentric distance (in accordance with Chandran et al 2011), at least in the slowest flows. On the other hand, Zhao et al (2019) found that the near-Sun proton temperature decreases with height as r −1 .…”
Section: Radial Evolution Of Contributions To the Solar Wind Energy Fluxsupporting
confidence: 87%
See 1 more Smart Citation
“…Under the assumption that, far from the Sun, faster wind is heated more than slower wind (Hansteen & Leer 1995;Totten et al 1995;Halekas et al 2023), our results explain qualitatively various interesting properties of observed temperature profiles. Close to the Sun, proton and minor-ion temperatures correlate positively with wind speed (Burlaga & Ogilvie 1973), while the electron temperature is negatively correlated (Marsch et al 1989); this is natural if the highly ), while the dashed line shows an f i that is independent of w ⊥ (as expected from stochastic heating).…”
Section: Discussionsupporting
confidence: 58%
“…The escaping population does not return to repopulate the sunward side of the electron VDF, resulting in a decrease in the phase space density on the sunward side (Jockers 1970;Landi et al 2012). This asymmetry, called a deficit or cutoff in energy, is set by the escape energy of electrons in the potential well, and it has been measured to empirically estimate the contribution of the ambipolar potential to the acceleration of the solar wind (Berčič et al 2020;Halekas et al 2020;Berčič et al 2021a;Halekas et al 2023). As an asymmetry in the local VDF, the deficit contributes to the heat flux in the near-Sun region (Halekas et al 2020(Halekas et al , 2023.…”
Section: Introductionmentioning
confidence: 99%